A MODULAR APPLICATION INTEROPERABLE PARADIGM FOR 5G EMPOWER FOG IOT (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
IoT is not a technology that works in isolation; It’s a hub where enabling technologies are connecting and provide servicing to each connected IoT based smart device.  Connecting devices are enormously increasing day by day; According to a global survey it is 10.07 billion in 2021, will expand to 13.15 billion in 2023 and approx. 24.44 billion in year 2030.  Such a huge web of interconnecting devices needs fastest generation of internet to accommodate each technology and provide fastest services; 5G accelerating such technologies and paved fully digitized and connected web of devices. Since IoT–Cloud integration with us so long and provides massive services in the field of Data management, analysis, and Business Intelligence; its advanced Fog-based architecture adopted by most of industries because of their quick response time and quality services.  In the Same way the migration of communication network from LTE 4 to 5G also offers lowest-possible latency, allows real-time delivery of data, increase of network flexibility and service availability especially for delay-sensitive services. The Migration of Cloud-IoT to Fog –based computing with 5G resolves the main issues of interoperability between these two technologies, which is a higher need of today’s IoT based industries and applications.
Keywords: IoT; Devices; 5G; Clouding computing